Financial problems associated with food insecurity among public university students in Peninsular Malaysia - Mohd Jamil, Nurulhudha; Sulaiman, Norhasmah; Adznam, Siti Nur ‘Asyura; Zainal Badari, Shamsul Azahari (Persatuan Pemakanan Malaysia, 2020)
Introduction: Food is a necessity for students. Yet, students’ food expenditure is anticipated to be restrained by their financial status. This cross-sectional study aims to determine the prevalence of food insecurity and its determinants among university students attending public universities in Peninsular Malaysia. Methods: Multistage random sampling was used to select respondents from public universities in Peninsular Malaysia. A total of 427 undergraduate students completed a selfadministered questionnaire at four randomly selected universities (Universiti Utara Malaysia, Universiti Kebangsaan Malaysia, Universiti Malaysia Pahang and Universiti Teknologi Malaysia). The questionnaire consisted of information concerning demographic and socioeconomic backgrounds, food security status, eating behaviour, financial literacy, and financial problem among university students. Frequency, chi-square, and logistic regression were used to analyse the variables. Results: Mean age of the respondents was 21.6 years, and 60.9% were found to be food insecure. Gender (χ2=5.415), origin (χ2=3.871), number of siblings (χ2=4.521), financial problem (χ2=42.364), and regular breakfast intake (χ2=5.654) were associated with food security status (p<0.05). Male respondents had 1.5 times (AOR=1.547, 95% CI: 1.006-2.380) the risk of having low food security status. Those with higher financial problems (AOR=3.575, 95% CI: 2.332-5.481) were 3.5 times more likely to be food insecure. Conclusion: The prevalence of food insecurity among public university students in Peninsular Malaysia was significantly high. Thus, intervention studies should focus on students with financial problems. Moreover, establishing a better system for an on campus food pantry or food bank is needed to counter the high prevalence of food insecurity among university students.